Molecular Architectonics : The Third Stage of Single Molecule Electronics - Ogawa, Takuji (Advances in Atom and Single Molecule Machines,, 2017)
This book draws on the main themes covered during the International Workshop on Molecular Architectonics which took place in Shiretoko, Japan from August 3 to 6, 2015. The concepts and results explored in this book relate to the term "molecular architectonics" which stands for electronic, optical and information-processing functions being orchestrated by molecular assemblies. This area is defined as the third stage of single-molecule electronics and builds on stage one, where measurements were performed on single-molecule layered films, and stage two, the resulting quantitative analyses. In this work, experts come together to write about the most important aspects of molecular architectonics. This interdisciplinary, visionary and unique book is of interest to scientists working on electronic materials, surface science and information processing sciences using noise and fluctuation.